Total Quality Management and Learning Organization for Early Childhood Education at PAUD ELPIST Temanggung - Asih Puji Hastuti; Sigit Tri Utomo (Journal of Childhood Development, 2022)
Abstract Educational problems related to the quality of education have been felt in line with the COVID-19 pandemic. In addition, there are problems related to the quality of education that does not increase even though the curriculum has been replaced with a new one, and there is a decline in the quality of education even though the level of teacher education is getting better. Another problem is the presence of new competitors, which causes many PAUD institutions to lose interest. This study aims to determine the management of PAUD implementation through the concept of Total Quality Management (TQM) and the Learning Organization of PAUD ELPIST Temanggung. The research method uses a qualitative descriptive approach. The subjects of this study consisted of principals, teachers, and staff of PAUD ELPIST Temanggung. Data collection techniques are observation, interviews, and documentation. Data analysis using data triangulation. The result of this research is that PAUD ELPIST Temanggung has implemented TQM by improving the quality of education on an ongoing basis with a priority strategy on customer needs. Furthermore, learning organizations have been used in organizational structure, information systems, human resource practices, organizational culture, and leadership.